2014
DOI: 10.1155/2014/501357
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Changes Associated with Increased Acid Resistance of Er:YAG Laser Irradiated Enamel

Abstract: Background. An increase in the acid resistance of dental enamel, as well as morphological and structural changes produced by Er:YAG laser irradiation, has been reported. Purpose. To evaluate the chemical changes associated with acid resistance of enamel treated with Er:YAG laser. Methods. Forty-eight enamel samples were divided into 4 groups (n = 12). Group I (control); Groups II, III, and IV were irradiated with Er:YAG at 100 mJ (12.7 J/cm2), 200 mJ (25.5 J/cm2), and 300 mJ (38.2 J/cm2), respectively. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 28 publications
1
15
0
2
Order By: Relevance
“…Similarly, mineralizing agents were used in the remineralization solution. These methods were used to efficiently identify calcium and phosphorus and indirectly study the mineral components on dental surfaces [16,[18][19][20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, mineralizing agents were used in the remineralization solution. These methods were used to efficiently identify calcium and phosphorus and indirectly study the mineral components on dental surfaces [16,[18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Bovine enamel was used as a model for human teeth. This model offers a large surface area and more uniform enamel thickness; previous studies have shown that they are very similar to human teeth [15][16][17].…”
Section: Introductionmentioning
confidence: 95%
“…There are limited reports regarding the element content in the same area of dental enamel during consecutive experimental phases (before and after treatment under several preventive protocols) [18,25]. Such analyses would allow for the objective measurement of the chemical changes that occur.…”
Section: Discussionmentioning
confidence: 99%
“…The distance between the tip and the sample was 1 mm, which was ensured by using a sheet of stainless steel (23 mm × 5 mm × 0 5 mm) that was fixed to the top of the laser handpiece. At this tip-sample distance, the exit tip and the laser beam had the same diameter, which was confirmed by a laminated infrared sensor screen (Lumitek International Inc., Ijamsville, MD, USA) [18,25,27,28]. Each sample was irradiated only once for 20 sec.…”
Section: Er:yag Lasermentioning
confidence: 94%
See 1 more Smart Citation